Retos y oportunidades en la aplicación del Código de Conducta de la CNUDMI para árbitros en la solución de controversias internacionales relativas a inversiones - Ampuero Llerena, Ricardo Manuel; Silva Escobar, Evelyn Lizbeth; Huaman Olivo, Soledad Yadhira (Pontificia Universidad Católica del Perú, 2025)
This article analyzes the UNCITRAL Code of Conduct for Arbitrators in International Investment Dispute Resolution in 2023. Based on a conceptual and regulatory review, it addresses key aspects of the instrument, such as the duty of continuous disclosure and restrictions on the simultaneous exercise of multiple roles (double hatting), along with an analysis of emblematic cases that reveal the importance of these rules. While the Code represents a step toward greater transparency and security, its implementation poses significant challenges, such as its coordination with existing regulatory frameworks, potential tensions with party autonomy, and uncertainty regarding the effectiveness of mechanisms to monitor compliance. In Latin America, and especially in Peru, its adoption could require institutional and regulatory adjustments to avoid an excessive reduction in the number of available professionals, allowing for the consolidation of a more accessible, representative, and reliable system.

El presente artículo analiza el Código de Conducta para árbitros en la solución de controversias internacionales relativas a inversiones aprobado por la CNUDMI en 2023. A partir de una revisión conceptual y normativa, se abordan aspectos clave del instrumento, como el deber de revelación continua y las restricciones al ejercicio simultáneo de funciones (double hatting), junto con un análisis de casos emblemáticos que revelan la importancia de estas reglas. Si bien el Código representa un avance hacia una mayor transparencia y seguridad, su implementación plantea retos importantes, como su articulación con los marcos normativos vigentes, posibles tensiones con la autonomía de las partes y la incertidumbre respecto a la eficacia de mecanismos para supervisar su cumplimiento. En América Latina, y especialmente en Perú, su adopción podría requerir ajustes institucionales y normativos que eviten una reducción excesiva del número de profesionales disponibles, permitiendo consolidar un sistema más accesible, representativo y confiable.
Challenges and opportunities in applying the UNCITRAL Code of Conduct for Arbitrators in International Investment Dispute Resolution
Keywords: Arbitration; Code of Conduct; Independence; Impartiality; UNCITRAL; ICSID; Double Hatting; Arbitraje; Código de Conducta; Independencia; Imparcialidad; CNUDMI; CIADI; Doble Sombrero; https://purl.org/pe-repo/ocde/ford#5.05.00